1994
DOI: 10.1007/bf02767729
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of urogenital malignancies in male patients undergoing maintenance haemodialysis

Abstract: We report two cases of urogenital malignancies, prostatic cancer in a 72-year-old man and urinary bladder carcinoma in a 50-year-old man, that developed during maintenance haemodialysis. The former patient responded to hormonal therapy with diethylstilboestrol and is still alive on maintenance haemodialysis, but the latter patient did not respond to treatment, being past cure in the far advanced stage. There are few clinical symptoms suggesting the existence of urogenital malignancies in dialysis patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although still open to debate, it has been reported that the incidence of malignancy is raised in hemodialysis patients compared to the general population 1–4 . Incidence of prostate cancer in hemodialysis patients has also been the target of debate and the rate of incidence depends on objective groups 2,4 .…”
Section: Discussionmentioning
confidence: 99%
“…Although still open to debate, it has been reported that the incidence of malignancy is raised in hemodialysis patients compared to the general population 1–4 . Incidence of prostate cancer in hemodialysis patients has also been the target of debate and the rate of incidence depends on objective groups 2,4 .…”
Section: Discussionmentioning
confidence: 99%
“…In hemodialysis patients, only a few cases of prostate cancer have been reported until recently. [1][2][3][4][5][6][7][8] The present report is probably the first case to show a complete response to lung metastasis of prostate cancer in a hemodialysis patient.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, most of the reports emphasized the difficulty of early detection of urogenital malignancies in hemodialysis patients due to a lack of clinical symptoms. [6][7][8] As for prostate cancer in hemodialysis patients, urologic symptoms are considered the same as in general patients. The symptoms of bone metastasis, however, run the risk of being misunderstood as renal-osteo disease in chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of prostate cancer in men receiving HD has been a target of debate, and the rate of incidence depends on group definitions [7,8,10] . Prostate cancer is the most common cancer in men and the second leading cause of death from cancer [2] .…”
Section: Discussionmentioning
confidence: 99%